Epidemiological surveillance of positive blood and cerebrospinal fluid cultures in the neonatal unit of Baragwanath's maternity hospital over a two year period, 1989-1990. - Funk, Evelyn Madeleine (My University, 1992)
The aims of this study were to establish the incidence of perinatally and nosocomially acquired bacteraemia and funqaemia as determinad by blood and cerebrospinal fluid (CSF) isolates in the neonatal population seen at the Baraqwanath Neonatal Unit; to identify risk factors for infection and record the outcome. Other aims were to analyze tha susceptibility patterns of the organisms isolated with respect to changing antimicrobial policies and to compare these with previously reported studies. (Abbreviation abstract)
A Dissertation submitted to the faculty of Medicine, University of the Witwatersrand, in partial fulfillment of the requirements for the Degree of Master of Medicine in paediatrics.
Keywords: Infant, Newborn, Diseases epidemiology.; Infant Mortality.